Psychosocial and discursive aspects in the appropriation of speech and written language (Olhar de Professor, 2024)
The central theme that drives this text is language, more specifically, speech and writing, with the aim of reflecting on psychosocial and discursive aspects present in the appropriation process. We seek to answer the following questions: how do psychosocial and discursive aspects overlap in the appropriation of speech and writing? How can teachers encourage this appropriation? We support our reflections on Historical-Cultural Psychology and the writings of the Bakhtin Circle, since these theoretical currents dedicate important reflections on language, placing it in the social field. Methodologically, we developed a theoretical-analytical study, as we are interested in explaining the approaches of these theoretical currents when dealing with the topic from a psychosocial and discursive perspective. Studies show that both speaking and writing are forms of language that can only be appropriated by the child if situated in interaction contexts, within which the child learns to speak and write.
Keywords: Language.; Appropriation of speech.; Appropriation of writing.